Morphogenesis and productivity of Pioneiro elephant grass under different residual heights and light interceptions - Sales, Eleuza Clarete Junqueira de; Saraiva, Carlos Ramon Santiago; Reis, Sidnei Tavares dos; Rocha Júnior, Vicente Ribeiro; Pires, Daniel Ananias de Assis; Vitor, Cláudio Manoel Teixeira (Acta Scientiarum. Animal Sciences, 2014)
The aim of this study was to assess two residual heights and two light interceptions on morphogenetic, structural and productive characteristics of Pennisetum purpureum Schum. cv. Pioneiro. The experiment was a factorial randomized block design with four replications. We evaluated morphogenetic characteristics in three basal tillers tagged in each plot, in different tussocks. Tiller population density was evaluated in marked areas in all experimental units. The interaction between the factors significantly influenced the leaf and pseudostem elongation rate, the leaf appearance rate, phyllochron, number of leaves per tiller, green leaves per tiller, final leaf blade length, leaf area index and biomass yield. There were no changes in the leaf senescence rate, number of senescent leaves per tiller and tiller density. Most morphogenetic variables was affected by the interactions between factors which also influenced the productivity, allowing to set the treatment with50 cm residual height and cut to reach values near 95% light interception as the one with the best results for the variables analyzed.